Neutrophil-to-Lymphocyte Ratio as a Prognostic Marker in Infective Endocarditis: In-Hospital and Long-Term Clinical Results - Bozbay, Mehmet; Ugur, Murat; Uyarel, Huseyin; Cicek, Gokhart; Koroglu, Bayram; Tusun, Eyyup; SÜNBÜL, MURAT; Murat, Ahmet; Sari, Ibrahim; Eren, Mehmet (My University, 2014)
Background and aim of the study: The neutrophil-to-lymphocyte ratio (NLR) is an independent predictor of poor prognosis in different clinical conditions such as infectious and cardiovascular diseases. It was hypothesized that a patient-s admission NLR would be predictive of an adverse clinical outcome in cases of infective endocarditis (IE).